Contribución al estudio de la fisiología del hombre andino - Exploración funcional del sistema nervioso extracardiaco del andino - Aste Salazar, J. Humberto (1936)
We began our studies in Lima (April 1934) with ocular-cardiac reflex, continuing at Chiclayo and Lambayeque (July-August 1934), which also made ​​observations on the average dynamic pressure and solar reflection.